2007
DOI: 10.1111/j.1745-6584.2006.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOSCREEN‐AT: BIOSCREEN with an Exact Analytical Solution

Abstract: BIOSCREEN is used extensively for screening-level evaluation of the transport of dissolved contaminants in ground water. The code has an effective graphical user interface that makes it ideal for use in both professional practice and as a teaching aid. BIOSCREEN implements the approximate transport solution of Domenico (1987). This note describes an enhanced version of the program, BIOSCREEN-AT, which supplements the Domenico solution with an exact analytical solution. The exact analytical solution has been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…6. As described in considerable detail in several recent reviews [38][39][40], the accuracy of the Domenico model depends mostly upon the value of longitudinal dispersivity and the position of the advective front of the plume. Since the problems presented in this study consider relatively short groundwater plumes because cleanup begins quickly after a spill occurs (e.g., 30 days), the modified Domenico model can be used because longitudinal dispersivity is small due to the short distance of the contamination plume.…”
Section: Contaminant Transport Modulementioning
confidence: 99%
“…6. As described in considerable detail in several recent reviews [38][39][40], the accuracy of the Domenico model depends mostly upon the value of longitudinal dispersivity and the position of the advective front of the plume. Since the problems presented in this study consider relatively short groundwater plumes because cleanup begins quickly after a spill occurs (e.g., 30 days), the modified Domenico model can be used because longitudinal dispersivity is small due to the short distance of the contamination plume.…”
Section: Contaminant Transport Modulementioning
confidence: 99%
“…Comparisons of those solutions to the one given by Domenico [11] revealed that simulated results can differ slightly, especially off the central plume axis [19,34,42]. This is why later, a new version of BIOSCREEN-AT was developed [24,27]. This version is based on the accelerated exact solution given by Neville [24,27] which can be evaluated in much less time than the one given earlier [29,43].…”
Section: Introductionmentioning
confidence: 95%
“…This is why later, a new version of BIOSCREEN-AT was developed [24,27]. This version is based on the accelerated exact solution given by Neville [24,27] which can be evaluated in much less time than the one given earlier [29,43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models, however, are restricted to modeling the transport of relatively few dissolved constituents in simplified systems. Despite these restrictions, analytical solutions are featured in popular spreadsheet tools such as the extensively used bioremediation tool, BIOSCREEN-AT (Karanovic et al, 2007) or the natural attenuation decision support system BIOCHLOR (Aziz et al, 2000;Clement et al, 2002). The ease of use and simplicity in modeling allow spreadsheet implementation of analytical models to serve as screening-level tools enabling decision makers to rapidly assess site conditions or investigate the need for higher model sophistication.…”
Section: Introductionmentioning
confidence: 99%